THE CONCEPT OF CHARACTER EDUCATION ACCORDING TO IMAM AL-GHAZALI AND ITS RELEVANCE TO MODERN ISLAMIC EDUCATION - Nur Wakhdatun Maolla; Erna Nur Komariah; Akhmad Affandi (COMPASS: Journal of Education and Counselling, 2025)
Character education is a fundamental aspect of the Islamic education system that aims to shape a holistic human being, not only in terms of intellect but also moral and spiritual dimensions. In the context of the current moral crisis affecting today’s youth, the thoughts of classical scholars such as Imam Al-Ghazali have become essential references to revitalize educational values. This study aims to examine the concept of character education in the thought of Imam Al-Ghazali and analyze its relevance to the modern Islamic education system. This research is qualitative in nature using a library research approach. The population includes all of Al-Ghazali’s writings related to education and ethics. The primary sample analyzed in depth is his monumental work Ihya’ ‘Ulum al-Din, which contains Al-Ghazali’s conceptual framework on soul purification (tazkiyat al-nafs), character development, and methods of value internalization. The instruments used are documentation techniques, data reduction, concept categorization, and content analysis of primary and secondary texts. The results show that Al-Ghazali viewed character education as a process of perfecting the soul through the instillation of faith, controlling desires, and habituating virtuous conduct through exemplary modeling and self-reflection (muhasabah). This concept remains relevant in addressing the challenges of modern Islamic education, particularly in forming well-rounded, ethical, and spiritually grounded students. This study recommends integrating Al-Ghazali’s values of character education into the curriculum and educational practices of contemporary Islamic institutions.